APPLICATION OF THE BASIC CONCEPTS OF ISLAMIC ECONOMICS TO THE EFFECTIVENESS OF SHARIA PROPERTY COMPANIES (International Conference on Social and Islamic Studies, 2022)
Economic activity according to Islamic view is an activity that is able to have a good impact on all people or society. It is hoped that with this economy, the prosperity and welfare of the community can be achieved and the benefits can be felt. The sharia economy upholds social values, where there is no difference in status, everyone has the right to get and feel prosperity and be free to be creative. Basically the principle of Islamic economics is concerned with the benefit of the people, not harm, so that the real goal for Islamic economics is to avoid chaos and riots. We know that almost all countries that have full power over the economy are the governments of these countries. Sharia property appears as the people's choice, especially for those who want to buy a house or just invest, making people, especially Muslims, feel much more comfortable because they can avoid usury, which is prohibited in Islam. Sharia property investment is property investment that is carried out on the basis of rules in accordance with religious rules, where everything you do must be in accordance including buying a house that will be used for investment. The purpose of this study is to find out how the application of the basic concepts of Islamic economics to the effectiveness of sharia property companies. This research is a study using a literature review. Literature review or literature research (literature review or literature research). The method of analysis in research with this literature review is descriptive analysis, namely the interpretation of ideas or information/data is carried out regularly and then given clear explanations so that they can be well understood.